Migrações internacionais de jovens rurais: limites da reprodução social de agricultores familiares e construções da autonomia pessoal / International migration of rural youth: limits of family farmers social reproduction and constructions of personal auto - Marin, Joel Orlando Bevilaqua; Drebes, Laila Mayara (Revista Brasileira de Sociologia - RBS, 2020)
O artigo tem como objetivo compreender o fenômeno das migrações internacionais vividas por jovens rurais, a partir da inter-relação de fatores objetivos e subjetivos que interferem na reprodução familiar de agricultores. A pesquisa foi realizada em Itapuranga, estado de Goiás, com base em dados qualitativos, obtidos por meio de entrevistas semiestruturadas. As migrações internacionais estão relacionadas com a desestruturação da produção agrícola e dos meios de vida dos agricultores familiares, que limitam a construção da autonomia dos jovens rurais e de processos de sucessão hereditária. Ancoradas em longa tradição, as migrações internacionais de jovens rurais passaram a representar estratégias de ascensão social, emancipação pessoal e transição para a vida adulta. In this article, we aim to analyze the phenomenon of international migrations experienced by rural young people, based on the interrelationship between objective and subjective factors that limit the traditional strategies of social reproduction in agriculture and the construction processes of social autonomy and entry into adult life. The research was carried out in Itapuranga, state of Goiás, Brazil, based on qualitative data, obtained through semi-structured interviews. International migrations are related to the disruption of agricultural production and the livelihoods of family farmers and to changes in perceptions of rural life and work, which limit the processes of hereditary succession and the construction of the autonomy of rural youth. Anchored in a long tradition, the international migrations of rural youth have begun to represent strategies of social ascension, personal emancipation and transition to adult life.